2019
DOI: 10.1111/vsu.13272
|View full text |Cite
|
Sign up to set email alerts
|

Standing MRI for surgical planning of equine fracture repair

Abstract: Objective To report the feasibility of standing MRI (sMRI) and document the value of sMRI in surgical planning for surgical repair of limb fractures in the horse. Study design Retrospective case series. Animals Thirty‐one horses with preoperative sMRI. Methods Medical records were reviewed for fracture type, application of a polyester cast, sMRI sequences performed, technical variables, and image quality. Fracture geometry and concomitant lesions were compared between sMRI and radiography. The relative value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Previous studies have reported complications such as further propagation or displacement of fractures [ 2 ] following induction of anaesthesia. This is mitigated against by providing external coaptation of the limb but complications can still occur.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have reported complications such as further propagation or displacement of fractures [ 2 ] following induction of anaesthesia. This is mitigated against by providing external coaptation of the limb but complications can still occur.…”
Section: Discussionmentioning
confidence: 99%
“…The two surgical plans were then compared and finally each case was classified in to three categories on the basis of the relevance of the CT study to surgical planning. These groups were defined by previously published parameters by Genton et al, 2019 [ 2 ]. These are as follows;…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neither imaging technique we used is able to detect cartilage lesions; however the addition of positive contrast arthrography can assist with identification of cartilage loss on CT examination [35]. Pre-operative standing MRI may be useful in determining Fx morphology and guiding surgical planning [6,36] yet movement can be an issue with standing MRI of the carpus. Arthroscopy is limited to diagnosis of injuries involving the joint surface.…”
Section: Discussionmentioning
confidence: 99%